Purification and the Secondary Structure of Fucoidanase from Fusarium sp. LD8. (1st October 2011) - Qianqian, Wu; Shuang, Ma; Hourong, Xiao; Min, Zhang; Jingmin, Cai
Abstract : The fucoidanase from Fusarium sp. (LD8) was obtained by solid-state fermentation. The fermented solid medium was extracted by citric acid buffer, and the extracts were precipitated by acetone and purified by Sephadex G-100 successively. The results showed that the specific fucoidanase activity of purified enzyme was 22.7-fold than that of the crude enzyme. The recovery of the enzyme was 23.9%. The purified enzyme gave a single band on SDS-PAGE gel, and the molecular weight of fucoidanase was about 64 kDa. The isoelectric point of the enzyme was 4.5. The enzyme properties were also studied. The results showed that the optimum temperature and pH were 60°C and 6.0, respectively; the temperature of half inactivation was 50°C, and the most stable pH for the enzyme was 6.0. K M, and the V max   of the enzyme was 8.9 mg · L −1 and 2.02 mg · min −1 · mL −1 by using fucoidan from Fucus vesiculosus as substrate. The compositions of the secondary structure of fucoidanase were estimated by FTIR, the second derivative spectra, and the curve-fitting analysis of the amide I bands in their spectra. The results showed that β -sheet was the dominant component (58.6%) and α -helix was the least (12%); the content of β -turn and random coil were 15.39% and 14.5%, respectively.